2018
DOI: 10.1111/cp.12103
|View full text |Cite
|
Sign up to set email alerts
|

Suicidal women may risk their lives but not their social relationships

Abstract: Objective Risk‐taking is an important but understudied suicidal factor, particularly concerning women. This study examined a broad range of risk behaviours and perceptions that might aid the early detection of suicidality by clinicians and gatekeepers. Method A purposive anonymous online survey, preferable for collecting data on stigmatised issues, produced a sample of 273 Australian/New Zealand women (aged 18–67 years) covering a broad spectrum of suicidal factors and risk‐taking behaviours. Participants comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 42 publications
(55 reference statements)
1
2
0
Order By: Relevance
“…One score increase in health risk tolerance was positively associated with a 17% increase in the incidence of suicidal ideation and 37% greater odds of having a greater level of suicidal ideation. This finding is in line with previous studies showing that people who have attempted suicide have greater risk tolerance (Colbert et al., 2021; Franklin et al., 2019; Huang et al., 2020; Pasculli & Harris, 2018). As suggested by the IPTS, a lack of fear of physical pain and death may be a key component in suicide.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…One score increase in health risk tolerance was positively associated with a 17% increase in the incidence of suicidal ideation and 37% greater odds of having a greater level of suicidal ideation. This finding is in line with previous studies showing that people who have attempted suicide have greater risk tolerance (Colbert et al., 2021; Franklin et al., 2019; Huang et al., 2020; Pasculli & Harris, 2018). As suggested by the IPTS, a lack of fear of physical pain and death may be a key component in suicide.…”
Section: Discussionsupporting
confidence: 91%
“…Health risk tolerance involves situations where an individual tolerates possible negative health consequences. Several studies have reported a positive link between positive risk attitudes and suicide (Colbert et al, 2021;Franklin et al, 2019;Huang et al, 2020;Pasculli & Harris, 2018). Franklin et al (2019) found that people who engaged in suicidal behaviors in virtual reality had significantly increased risk-taking, including risk-taking in the health domain, than those who did not engage in suicidal behaviors.…”
Section: Tolerance Of Health Riskmentioning
confidence: 99%
See 1 more Smart Citation